The effect of a safety crisis on safety culture and safety climate: The resilience of a flight training organization during COVID-19. (March 2022) - Byrnes, Kenneth P.; Rhoades, Dawna L.; Williams, Michael J.; Arnaud, Anke U.; Schneider, Andrew H.
Abstract: Flight training programs incur great risks as they instruct aspiring pilots to complete flight training and licensing procedures. It is instrumental for these programs to create strong safety cultures and climates to promote the highest level of safety possible. The COVID-19 pandemic raised many safety concerns across a variety of industries, especially the aviation industry. This study investigates the impact that the COVID-19 pandemic had on the safety culture and safety climate of the flight training organization at Embry-Riddle Aeronautical University (ERAU). For this purpose, we collected longitudinal data for the years 2018 through 2021 including the variables of safety culture and safety climate. The results of this research suggest that various safety culture and safety climate variables were impacted during the COVID-19 pandemic. Based on these results, leadership of the flight training program was able to mitigate and adjust safety policies and procedures to improve the safety culture and climate and ensure continuous accident-free performance. Finally, the viability of these and other safety procedures for the safe management of future crises are discussed.